Modernity and Contemporaneity - Arabatzis, Georgios (Hellenic-Serbian Philosophical Dialogue Series, 2022)
Modernity and Contemporaneity is the 3rd volume in the Hellenic-Serbian Philosophical Dialogue Series, a project that was initiated as an emphatic token of the will and commitment to establish permanent and fruitful collaboration between two strongly bonded Departments of Philosophy, this of the National and Kapodistrian University of Athens, and that of the University of Novi Sad respectively. This collaboration was founded from the very beginning upon friendship, mutual respect and strong engagement, as well us upon our firm resolution to establish a solid continuity in the editing project. The publication of this volume allows us to entertain feelings of contentment and confidence that this objective of the project has been accomplished.